2023
DOI: 10.55115/edukasi.v4i1.2727
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Value Clarification Technique (VCT) Berorientasi Tri Hita Karana Terhadap Sikap Spiritual Dan Sikap Sosial Mahasiswa

Abstract: The purpose of this study was to see the effect of the Tri Hita Karana-oriented Value Clarification Technique (VCT) learning model on the spiritual attitudes and social attitudes. The sample in this study were students of class G and B semester I of the PGSD Department in the 2022/2023 school year. This type of research is quasy experimental research. The data method used in this research is the observation method and the questionnaire method. Observation methods and questionnaires were used to collect data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The dominant factor in the formation of tolerance is the factor of the accuracy of the implementation of the learning activity strategy, namely the value clarification learning activity strategy. In line with the results of research (Nirmayani & Yudiana, 2023), the VCT strategy can reduce social behavior that is not good that society does not want. (Merian et al, 2019) In his research, he concluded that value clarification strategies with various variations can increase students' understanding of morals, behavior, and independence.…”
Section: Discussion the Impact Of Learning Strategies In The Developm...supporting
confidence: 68%
See 2 more Smart Citations
“…The dominant factor in the formation of tolerance is the factor of the accuracy of the implementation of the learning activity strategy, namely the value clarification learning activity strategy. In line with the results of research (Nirmayani & Yudiana, 2023), the VCT strategy can reduce social behavior that is not good that society does not want. (Merian et al, 2019) In his research, he concluded that value clarification strategies with various variations can increase students' understanding of morals, behavior, and independence.…”
Section: Discussion the Impact Of Learning Strategies In The Developm...supporting
confidence: 68%
“…The results of the research showing the advantages of implementing the VCT strategy include research by (Ima et al, 2023;Nirmayani & Yudiana, 2023;Yusrizal & Hariati, 2022) which concluded that the VCT learning activity strategy can evoke an understanding of the value of appreciating hero service. The results of experimental research (Asikin et al, 2021;Dewantoro & Sartono, 2019;Ula et al, 2020) show the VCT method's superiority over conventional methods, which concludes that the VCT model can improve student character.…”
Section: Values Clarification Technique (Vct)mentioning
confidence: 84%
See 1 more Smart Citation